Vicoa sahyadrica (Asteraceae), a new species from Western India with a note on Dalzell’s Vicoa cernua and Heracleum grandiflorum - Nandikar, Mayur D.; Sardesai, Milind M. (Phytotaxa, 2021)
Recently described two new species, viz. Pinda shrirangii (Apiaceae) and Vicoa gokhalei (Asteraceae), are reviewed for their taxonomy. An illegitimate Heracleum grandiflorum Dalzell & Gibson (non Steven ex M. Bieb.) is recognised as conspecific with P. shrirangii and proposed as a new synonym of the latter. Vicoa gokhalei is found to be conspecific with V. cernua Dalzell. Consequently, Vicoa cernua sensu Gosavi et al. with inconspicuously ligulate ray florets and more pappose achenes is described here as a new species, viz. Vicoa sahyadrica Nandikar & Sardesai.